Chromosome 2q12.3-q13 copy number variants in patients with neurodevelopmental disorders: genotype-phenotype correlation and new hotspots. (15th July 2022) - Aarabi, Mahmoud; Baumann, Jacqueline; Babcock, Melanie; Kessler, Elena; Sebastian, Jessica; Madan-Khetarpal, Suneeta; Hu, Jie; Ou, Zhishuo; Yatsenko, Svetlana
Abstract : Introduction: The complex structure of the chromosome 2q12.3-q13 region provides a high chance of recombination events between various low copy repeats (LCRs). Copy number variants (CNV) in this region are present in both healthy populations and individuals affected with developmental delay, autism and congenital anomalies. Variable expressivity, reduced penetrance and limited characterization of the affected genes have complicated the classification of the CNVs clinical significance. Methods: Chromosomal microarray analysis data were reviewed for 10 298 patients with neurodevelopmental disorders referred to the UPMC Medical Genetics and Genomics Laboratories. A genotype-phenotype correlation was performed among the patients harboring the 2q12.3-q13 CNVs with overlapping genomic intervals. Results: We identified 17 (1 in 600) individuals with rare CNVs in the 2q12.3-q13 region, including nine patients with deletions, seven individuals with duplications and one patient who had both a deletion and a duplication. Likely pathogenic CNVs with the breakpoints between LCRs encompassing the potential dosage-sensitive genes BCL2L11, BUB1, FBLN7 and TMEM87B were the most common. CNVs were also observed between LCRs surrounding the RANBP2 and LIMS1 genes. Conclusion: Our study provides evidence for pathogenic CNV hotspots within the chromosome 2q12.3-q13 region. We suggest CNV classification based on the affected interval and the involvement of potential dosage-sensitive genes in these patients.